2015
DOI: 10.1257/aer.20130623
|View full text |Cite
|
Sign up to set email alerts
|

Clientelism in Indian Villages

Abstract: We study the operation of local governments (Panchayats) in rural Maharashtra, India, using a survey that we designed for this end. Elections are freely contested, fairly tallied, highly participatory, non-coerced, and lead to appointment of representative politicians. However, beneath this veneer of ideal democracy we find evidence of deeply ingrained clientelist vote-trading structures maintained through extra-political means. Elite minorities undermine policies that would redistribute income toward the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 27 publications
5
115
0
Order By: Relevance
“…200 (˜$3) per month except for disability 6 Imperfect implementation of social insurance programs may even be a deliberate choice by local elites to preserve their power over the rural poor, as they are often the default providers of credit and insurance. See Anderson et al (2013) for discussion, and also Jayachandran (2006) who shows how uninsured rainfall shocks benefit landlords and hurt workers (especially those who lack access to credit).…”
Section: Social Security Pensionsmentioning
confidence: 99%
“…200 (˜$3) per month except for disability 6 Imperfect implementation of social insurance programs may even be a deliberate choice by local elites to preserve their power over the rural poor, as they are often the default providers of credit and insurance. See Anderson et al (2013) for discussion, and also Jayachandran (2006) who shows how uninsured rainfall shocks benefit landlords and hurt workers (especially those who lack access to credit).…”
Section: Social Security Pensionsmentioning
confidence: 99%
“…The data reveal that where political contestation using vote buying strategies is more widespread, politicians reduce investments in those service delivery instruments-in primary health-that are particularly likely to be broadly pro-poor in delivering benefits. Anderson, Francois, and Kotwal (2015) show that weakening enfranchisement through clientelist relations between land-owning elite families and agricultural households in Indian villages is associated with lower public investments in social safety nets and antipoverty programs. In related results, Baland and Robinson (2006) find historical evidence that the introduction of the secret ballot in Chile was associated with a decline in votes for right-wing parties and a drop in the price of land (both of which are consistent with a reduction in the power of clientelist relations).…”
Section: Problem Of Preferencesmentioning
confidence: 96%
“…While there is a lot of work examining the details of clientelist political transactions, and its political outcomes, there is relatively little work on implications of clientelist politics for the incentives of leaders who wield powers over policy-making. Although there are some theories about the negative consequences of clientelist politics for policy selection in equilibrium (Baland and Robinson, 2006;Bardhan and Mookherjee, 2012;Anderson et al, 2015), it is also conceivable that vote buying could be a form of political responsiveness to the demands or needs of voters. Gift-giving at election times and service delivery in between elections may be positively correlated, simultaneously driven by underlying conditions of demanding citizens and political contestation.…”
Section: Problem Of Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Besley et al, on the other hand, found in their survey of four southern states (Karnataka, Andhra Pradesh, Kerala, and Tamil Nadu) in India that both intra-and inter-village resource allocations were clearly driven by the self-interest of the political elite. 20 This is not to say that decentralization has had no beneficial effects for the 22 In a study of local governance in Maharashtra conducted between 2007 and 2008, they find that democracy is alive and well in form but not in substance. In panchayat (village government) elections, the voter turnout is impressive (over 90 percent), the reservation policy for women and scheduled castes and tribes is strictly implemented, and yet poverty alleviation schemes that would benefit the majority are conspicuous by their absence in the panchayat agenda.…”
Section: Are Indian Institutions Extractive? Is This Why They Are Permentioning
confidence: 99%